2006
DOI: 10.1007/s10508-006-9065-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Differential Viewing Patterns to Erotic and Non-Erotic Stimuli Using Eye-Tracking Methodology

Abstract: As a first step in the investigation of the role of visual attention in the processing of erotic stimuli, eye-tracking methodology was employed to measure eye movements during erotic scene presentation. Because eye-tracking is a novel methodology in sexuality research, we attempted to determine whether the eye-tracker could detect differences (should they exist) in visual attention to erotic and non-erotic scenes. A total of 20 men and 20 women were presented with a series of erotic and non-erotic images and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
87
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 24 publications
(24 reference statements)
8
87
2
Order By: Relevance
“…Motivated by the suggestion that our gaze behavior in viewing scenes of high ecological validity is guided by interest (Henderson, 2003;Issacowitz, 2006) A few recent studies also observed that heterosexual men directed more visual attention to opposite sex figures in both erotic and non erotic stimuli (Lykins et al, 2006(Lykins et al, , 2008Rupp & Wallen, 2007). However, some of these studies used relatively crude measures to define where the observer was viewing (i.e., face, body, genitals, background) (Lykins et al, 2006(Lykins et al, , 2008Rupp & Wallen, 2007), offering little insight into which body regions were crucial in this visual assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by the suggestion that our gaze behavior in viewing scenes of high ecological validity is guided by interest (Henderson, 2003;Issacowitz, 2006) A few recent studies also observed that heterosexual men directed more visual attention to opposite sex figures in both erotic and non erotic stimuli (Lykins et al, 2006(Lykins et al, , 2008Rupp & Wallen, 2007). However, some of these studies used relatively crude measures to define where the observer was viewing (i.e., face, body, genitals, background) (Lykins et al, 2006(Lykins et al, , 2008Rupp & Wallen, 2007), offering little insight into which body regions were crucial in this visual assessment.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these studies used relatively crude measures to define where the observer was viewing (i.e., face, body, genitals, background) (Lykins et al, 2006(Lykins et al, , 2008Rupp & Wallen, 2007), offering little insight into which body regions were crucial in this visual assessment. Other researchers did not compare viewing strategies to different aged figure images (Hewig et al, 2008) or gender (Cornelissen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In self-report measures of emotion, negative stimuli also tended to be assessed using more extreme scores for arousal than did positive stimuli (e.g., Bradley et al, 2001;Cacioppo, Gardner, & Berntson, 1997). Erotic voice stimuli seem to represent the only exception, rated as being as arousing as angry voice stimuli, especially if spoken by actors of the opposite rather than the same sex as the listener (e.g., Ethofer et al, 2007), and as being more arousing than other pleasant stimuli (e.g., Bradley, Codispoti, Cuthbert, & Lang, 2001;Lang, Bradley, Fitzsimmons, Cuthbert, Scott, Moulder, & Nangia, 1998;Lykins, Meana, & Kambe, 2006).…”
mentioning
confidence: 99%
“…Furthermore, there has been no study to investigate this relation in men with an eye-tracking system as a reliable methodology for assessing visual attention to sexual stimuli, with which we and other researchers have reported a sex difference in sexual interest. 2,6,7 We found clearly by using Pearson's correlation coefficient in this study that, as the degree of paranoia, psychasthenia and social introversion in Sexual interest and personality characteristics in men A Tsujimura et al the personality grew stronger, sexual interest in the sexual region became weaker. Paranoia is a psychology characterized by excessive anxiety or fear.…”
Section: Discussionmentioning
confidence: 50%